On the line shift and oscillator strength of Xe II lines in the spectra of HnMn stars - Di Rocco, Héctor O. (2015)
Aims. The ultimate goal that has motivated this work is to achieve realistic oscillator strength (gf) values to find reliable values of stellar abundances. We aim to compare the gf valúes of Xe ii lines found with different theoretical and experimental methods. Methods. We have undertaken calculations using the quasirelativistic and relativistic Hartree-Fock methods. Then we compare these results with those previously obtained from UVES spectra of HgMn stars. Results. 1) Our theoretical gf values are more realistic than those previously obtained for most lines. When we consider only unblended, isolated, relatively noise-free lines, however, our theoretical gf values and Yuce's stellar values differ little from each other. 2) In a discussion of the origin of the previously observed discrepancy between the wavelengths of Xe ii lines deducted from stellar spectra and those published by National Institute of Standards and Technology (NIST), we conclude that stellar wavelengths could be considered the standard wavelengths whenever the densities in stellar atmospheres are smaller than 1 × 1016 part. cm-3.